(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
The process of construction semi-flexible pavement involves using a combination of a porous asphalt mixture and certain grouting material. This pavement has favourable mechanical characteristics and able to withstand heavy traffic load without premature failure. Grouting materials are crucial in constructing of semi-flexible pavement as they are responsible for filling and reinforcing the asphalt mixture, resulting in gaining high-performance pavement. Prior research has shown its versatility in many applications, including roads, motorways, bridge deck pavement, tunnels, and industrial zones with heavy industrial equipment traffic, airport aprons, and stations. This study aims to identify and collect the most important research papers utilizing the Web of Science (WOS), then analyze the data using the VOS viewer program to identify the importance and extent of researchers’ interest in this topic, as well as identify most of the countries and journals that have published about the design, construction, and installation of semi-flexible pavements. As well as the authors and their collaboration, in addition to knowing the keywords that help researchers and authors in researching this topic. It is essential to use these studies to obtain a deeper understanding of the factors that affect the performance of mixtures and semi-flexible mortars, such as material gradation, porous asphalt mixtures, and components of grout materials.